2011
DOI: 10.1007/s11027-011-9337-3
|View full text |Cite
|
Sign up to set email alerts
|

Evolving local climate adaptation strategies: incorporating influences of socio–economic stress

Abstract: Socio-economic and climatic stresses affect local communities' vulnerability to flooding.Better incorporation of socio-economic stress in local vulnerability assessments is important when planning for climate adaptation. This is rarely done due to insufficient understanding of their interaction, in both theory and practice. The omission leads to critical weaknesses in local adaptation strategies. This study analyses how socioeconomic stress interacts with climatic stress and shape local vulnerability to floodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…Research into coping with multiple stresses has challenged perceptions about those most vulnerable to environmental stress, showing the need to consider those directly and indirectly affected (Hjerpe and Glaas 2011;Quinn et al 2011). If focuses on the socio-economic factors identified in this review as important for coping, such as livelihood activity and wealth, and how these factors shape the response to different hazards.…”
Section: Coping With Climate Induced Hazards In Rural Households In Umentioning
confidence: 99%
“…Research into coping with multiple stresses has challenged perceptions about those most vulnerable to environmental stress, showing the need to consider those directly and indirectly affected (Hjerpe and Glaas 2011;Quinn et al 2011). If focuses on the socio-economic factors identified in this review as important for coping, such as livelihood activity and wealth, and how these factors shape the response to different hazards.…”
Section: Coping With Climate Induced Hazards In Rural Households In Umentioning
confidence: 99%
“…The first step was to assess current adaptation approaches using a meta-evaluation of existing single and cross-case studies published between 2008 and 2013 [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. These studies were identified through searching databases of scientific articles using the following search string: adaptation AND (Sweden OR Swedish) AND (urban OR city OR cities OR municipa*).…”
Section: Methodsmentioning
confidence: 99%
“…Others take out insurance to be prepared for liability claims from disaster-affected citizens [24] (this measure is, however, a grey zone and could alternatively be classified as internal mainstreaming). Table 1 Apart from the proactive strategies identified to push forward the integration of adaptation at institutional level and thereby assure adaptive and disaster-resilient developments on the ground, a range of opposite strategies was also found (Table 4).…”
Section: Institutionalizing Adaptation In Municipalities' Day-to-day mentioning
confidence: 99%
See 1 more Smart Citation
“…Coastal communities are particularly sensitive to the impacts of climate change, which has led to increasing storm events, storm surges, and erosion and impacts on infrastructure, saltwater intrusion into freshwater areas, impacts on ecosystems and species that are important for livelihoods, and changes in seasons and rainfall patterns leading to less predictability (see McClanahan & Cinner, 2011). Explicit recognition of multiple stressors and socio-economic stress is essential for successful adaptation planning and policy (Hjerpe & Glaas, 2012). The theory of "double exposure" recognizes that there are multiple stressors that are simultaneously impacting individuals, communities, groups, or sectors and interacting to produce both positive and negative outcomes (Leichenko & O'Brien, 2008;O'Brien & Leichenko, 2000).…”
Section: Theoretical Framework: Vulnerability To Multiple Stressorsmentioning
confidence: 99%